Physical and Mechanical Properties of Particleboard Made from Jatropha (Jatropha curcas) Fruit Hulls Reinforced with Wood Particle - Apri H Iswanto; Fauzi Febrianto; Yusuf Sudo Hadi; Surdiding Ruhendi; Dede Hermawan (Masyarakat Peneliti Kayu Indonesia, 2012)
The objective of this research was to evaluate the properties of particleboard made from mixtures of jatropha fruit hulls (JFH) and wood particle in several mixture ratios. JFH, and mangium wood (Acacia mangium Wild) particle were untreated and treated with 1% acetic acid solution for 24 h. Urea formaldehyde (UF) resin with 10% resin content (SC: 63%) was used as binder. The ratio of JFH and wood particles were set at 100:0, 70:30, 60:40, 50:50, and 0:100. The target density of particleboard was set at 0.70 g cm-3. The temperature and pressure of hot pressing were set at 130 ºC and 2.544 N mm-2 for 10 minutes. The physical and mechanical properties of particleboard were evaluated according to JIS A 5908-2003 standard. The result indicated that addition of untreated mangium wood particle onto JFH particles improved mechanical properties of board especially modulus of elasticity (MOE) and modulus of rupture (MOR) parameters. However, the internal bond (IB) parameter was found to decrease with addition of wood particle. The higher amount of wood particle added resulted in the better the MOR and MOE parameters. Addition of acetic acid treated mangium wood particle onto JFH particleboard resulted in lower physical and mechanical properties.Key words: Jatropha curcas, fruit hulls, particleboard, wood particle